HEPARIN INDUCED THROMBOCYTOPENIA AND HEMODIALYSIS - ELHASSADE, AMAL S.; NASER, AHLAM MOHAMED BEN (International Journal of Clinical and Biomedical Research, 2016)
Unfractionated heparin is the most commonly used anticoagulant for hemodialysis (HD). It is well-known that heparin can cause immune-mediated thrombocytopenia due to immunoglobulin antibody formation against the complex of platelet factor 4 (PF4) and heparin. Heparin may also contribute to HD-associated platelet activation, thrombocytopenia, and increased PF4 release from platelets during a heparin dialytic session. The present study was conducted to study the effect of unfraction heparin as anticoagulant in newly treatment hemodialysis patients. Material and method: A sample of 72 people were selected, 32 patients on dialysis for first time from unite of kidney dialysis. At the same time a group of 40 randomly selected healthy adults to participate in the study as control. By Automated cell counter (sysmex X 21) platelets from all patients on dialysis before starting heparin and after one month later were estimated. Result: The mean value of platelets in patients after treated with heparin was significant lower (192.3 ± 20.7 ) — 109/l as compare before treated with heparin 203 ± 20.7 — 109/l ( P = 0.001). Conclusion: From this study, heparin as anti-coagulant has effect on decrease platelets count but still patients have no thrombocytopenia platelets level 150 — 109/l.h